ANALISIS KETERLAMBATAN BAHASA PADA ANAK - Siti Anisatun Nafi'ah; Nuril Maghfiroh (As-Sibyan, 2020)
The growth of language have biggest contribution to support the other growth. Accordingly, the growth of language in early child is important point to noticed. This aim of research to know type delay of language and factor of cause it. This research use qualitative of research type with approach of case study. The collecting of data in this research use interview, observation, and documentation. The based of result research indicate that he suffer delay of language type receptive. It was indicated when he communicate with his friend only use smile and body language. He seldom speech long sentence. The result of analyze indicate that heredity and sex affect his delay of language.